PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA ANGGOTA MELALUI KOMPETENSI PADA PUSLATDIKSARMIL SIDOARJO - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
This study aims to examine and analyze the effect of education and training on the performance of members of the Military Basic Training and Education Center (Puslatdiksarmil) in Sidoarjo through competence variables. Data was collected through the distribution of questionnaires and carried out to 129 members of the Puslatdiksarmil in Sidoarjo. The results show that directly the education variable, training variable and competence variable have a significant effect on performance, education variable has no significant effect on performance through competence, training variable has a significant effect on performance through competence, so the role of leadership is needed in efforts to improve education, training and competence. all members of the Puslatdiksarmil periodically to improve their performance. The implication of this research is that education and competence play an important role in improving the performance of members directly, training through competence plays a very important role in improving the performance of members so that organizational goals are expected to be achieved.